Colored Pencil Basics - Knox, Cynthia (Califarnia Walter Foster, 2012)
LEARING BASIC techniques - drawing from photograhs workinf\g with color - achieving accurate proportions
Arts (Drawing)
13
Keywords: Colored pencil drawing -- Technique; Drawing